La thèse du « génocide indien » : guerre de position entre science et mémoire - Frédéric Dorel (Amnis)
“Native American Genocide” and “Native American Holocaust” are expressions that are currently and widely used to define the destruction of the aboriginal populations of America after the arrival of the Europeans. But the numerous and various massacres of Native populations are not listed among the genocides officially acknowledged by the United Nations. Many observers strongly resent this as an injustice, others favour a less emotional analysis. Their debate reflects the conflict of two different visions of history, two opposite understandings of the past. One is justified by grief and memory; the other – more scientific and ethnological – explains that while crimes against humanity clearly occurred, the extinction of 90% of the pre-Columbian populations should more appropriately be termed ethnocide rather than genocide. The difference between both concepts stems neither from the number of victims – countless in both cases – no the final objective – identical, but rather in the elements destroyed. Destruction of the individuals on the one hand, destruction of the cultures on the other hand. The aim of this paper is to explore the main points of both sides of the debate, and to attempt to sort out the rightful legal recognition of memory from the rightful scientific and historical understanding of the events.